Cost effectiveness of anticipatory action: Lesotho, Madagascar, and Mozambique - de Brauw, Alan (CGIAR System Organization, 2025)
An important question when conducting anticipatory action programs relates to its cost-effectiveness. By cost effectiveness, we refer to the relative costs and benefits of anticipatory action in general relative to a more standard approach to post-shock aid. In this context, we largely want to know what would happen to potential beneficiary households in two different scenarios: 1) if they receive anticipatory action transfers, and 2) if they instead receive unconditional post-shock transfers of the same size. The idea is that we assume there is a fixed budget envelope, and the same amount of assistance could be provided as either anticipatory action or as post-shock transfers. The resulting measurement estimates the difference in benefits and losses to providing anticipatory action relative to post-shock assistance, providing a conclusion on the overall net benefits or losses of this approach. Since we assume a fixed budget envelope, we invert the process of measuring cost effectiveness by measuring the net benefits of anticipatory action relative to post-shock transfers. This analysis uses the conceptual framework developed by de Brauw and Bloem (2024) to identify classes of potential benefits and costs for anticipatory action relative to unconditional post-shock transfers. The model suggests the main benefit to anticipatory action is that households can better protect their productive asset holdings, whether livestock or other farm implements, which implies their future incomes will be higher than they would be otherwise. There are also potential gains for households during the negative shock, implying those households may be less food insecure, for example, while the shock is occurring.1 On the other hand, the framework suggests that a specific cost to anticipatory action is the cost of getting it wrong (i.e., giving people benefits when the shock does not materialize for those people).